Green Synthesis of Gold Nanoparticles Using Basella alba Leaf Extract and Their Antioxidant Activity - Nur Rizka Aprilia; Titik Taufikurohmah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
In this research, gold nanoparticles were synthesized using the green synthesis method with the bioreduction extract of Basella alba leaf infusion. This research aims to characterize gold nanoparticles synthesized using UV-Vis spectroscopy and TEM and assess their antioxidant activity, which is quantified by the IC50 value. The UV-Vis spectrophotometric characterization of the gold nanoparticles revealed an absorption peak at a maximum wavelength of 543 nm. TEM characterization indicated a particle diameter of 9.463 ± 2.273 nm. The antioxidant activity was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) reduction method with concentration variations of 2.5, 5, 10, and 20 ppm, resulting in reduction percentages of 40.6%, 44.3%, 57.4%, and 77.9%, respectively, and an IC50 value of 7.05 μg/mL, indicating very strong antioxidant activity. Based on these findings, it can be concluded that Basella alba leaf infusion extract is effective as a biological reducing agent in synthesizing gold nanoparticles, and the resulting nanoparticles show significant potential as antioxidants for reducing free radicals.